Barriers to Service Provision for Justice-Involved Youth - Kapoor, Anjani (Criminal justice and behavior, 2018)
Despite robust evidence for the efficacy of the Risk-Need-Responsivity (RNR) framework, the needs of youth on community supervision, as identified by risk-need assessments, are frequently not reflected in the services they receive. Potential barriers to recommended service were examined in 219 Canadian youths who were court-ordered to receive forensic assessments. Decreased service was associated with certain criminogenic needs (e.g., antisocial attitudes, substance abuse) that were treatment impeding in nature. Lower treatment receipt was also associated with youth whose parents were detached from the probation process. Furthermore, odds of recidivism increased when youth experienced more lifestyle destabilizers, capacity issues, and systemic barriers, even after accounting for the effect of receiving intervention for identified criminogenic needs. Results suggest the importance of addressing both criminogenic and noncriminogenic factors during probation sentences and call for greater adherence to, and expansion of, the responsivity principle to include the assessment and management of destabilizing and systemic factors.